Wind turbine optimization through optimal blade shape design for low wind speeds - Tira, H.S.; Juliawan, Y.; Padang, Y.A.; Nurpatria, N. (Dinamika Teknik Mesin, 2023)
Current electricity needs continue to rely on depleting fossil fuels such as fossil fuel and coal. The current government effort is to find non-fossil fuel alternative energy sources. Wind energy is one of the efforts to use ecologically friendly renewable alternative energy. Studies on the development and use of new and renewable energy are now undertaken. One of them is a series of research on the utilization of wind in numerous places of Indonesia through the construction of wind turbines. The blade that explicitly makes contact with the wind is one of the most critical sections of a wind turbine. The shape of the airfoil determines whether or not the blade is used. The focus of this research was to determine the optimal type of airfoil by comparing the coefficient of power (Cp), maximum power, and lowest power produced by various NACA (National Advisory Committee for Aeronautics) airfoils. NACA 4410, 4412, and 4415 airfoils were employed in this study.